Tingkat Kecukupan Fasilitas Praktikum di Laboratorium (Bengkel) Teknik Permesinan SMK Piri 1 Yogyakarta Tahun Ajaran 2020/2021: Tingkat Kecukupan Fasilitas Praktikum di Laboratorium (Bengkel) Teknik Permesinan SMK Piri 1 Yogyakarta Tahun Ajaran 2020/2021 - muhammad muhyi; subagyo subagyo; arif bintoro johan (JURNAL VOKASI DEWANTARA (JVD), 2022)
This study aims to determine the adequacy level of practicum facilities in the machinery laboratory (workshop) at the Mechanical Engineering Expertise Program at SMK Piri 1 Yogyakarta based on the standards required by PERMENDIKNAS RI No. 40 of 2008. This research is a descriptive study. Respondents in this study were the head of the department and 2 teachers of the Mechanical Engineering Expertise Program, and the infrastructure in the machining workshop, especially in terms of the machinery workshop building, machinery workshop furniture, machinery workshop equipment, machine workshop educational media, and other machinery workshop equipment. Data collection techniques by means of observation, interviews, and documentation. The instrument uses a checklist used in the observation with the Rating Scale model rating scale. The results showed that the level of achievement in terms of machining workshop infrastructure was 80.88% (very feasible). The level of achievement in terms of machining workshop facilities is 85.52% (very feasible). The overall level of achi evement of machining workshop facilities is 82.14% (very feasible).